Strategic leadership strategies of village heads in driving sustainable tourism village development - Lestari, Sri (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2025)
The transformation of a village into a tourist village is a complex and multidimensional process that requires effective leadership, community empowerment, and synergy among local stakeholders. This study aims to analyze the role of the village head in directing policies, managing community participation, and optimizing local resources in the transformation of Lerep Village, Semarang Regency, into a community-based tourism destination. Using a qualitative approach with a case study design, data were collected through in-depth interviews with the village head, community leaders, and tourism practitioners; participatory observations of village activities; and analysis of policy documents and empowerment programs. Data analysis was conducted using the Miles and Huberman (1984) model, involving data reduction, presentation, and conclusion drawing with source, technique, and time triangulation to enhance the validity of the findings. The results of the study show that the leadership of the village head is both participatory and transformational. Participatory leadership is reflected in village deliberation forums and inclusive decision-making mechanisms, while transformational leadership is seen in the development of unique tourism products, community-based training, and cross-sector collaborations that strengthen community independence. The combination of these two leadership styles increases citizen participation, strengthens local institutions, encourages innovation, and produces positive socio-economic impacts, such as increased income for micro-enterprises and strengthened social cohesion. In conclusion, the role of the village head is not only as an administrative figure but also as a catalyst for change capable of integrating the values of mutual cooperation with modern leadership strategies. This study contributes to the development of a tourism village leadership model that can be applied in various other contexts to promote inclusive, participatory, and sustainable village development.